A double-blind, randomized, placebo-controlled trial of short- and extended-regime antibiotics in infection rates after open reduction and internal fixation of uncomplicated single mandibular fractures. Issue 3 (May 2015) - Dogra, Suruchi; Bhutia, Ongkila; Nagori, Shakil Ahmed; Roychoudhury, Ajoy; Jose, Anson; Das, Bimal K.; Pandey, Ravindra M.
Abstract Purpose To compare short- and extended-regimen post-operative antibiotic prophylaxis after open reduction internal fixation (ORIF) of single uncomplicated mandibular fractures. Subjects and methods A prospective, single centre, randomized, double-blinded, placebo-controlled study was carried out where 39 patients with single uncomplicated mandibular fractures were treated by an intra-oral approach. They were divided into two groups: group 1 (20 patients) and group 2 (19 patients). Each group received injection amoxicillin + clavulanic acid (30 mg/kg/day) pre-operatively, intra-operatively and for 24 h post-operatively. Group 1 then received placebo and group 2 received oral amoxicillin + clavulanic acid (30 mg/kg/day) in two divided doses for the next 4 days. The patients were evaluated on the 3rd and 7th post-operative day for signs of clinical infection and suture site aspirates were collected for culture. Microbial load was evaluated against the presence or absence of clinical infection in both the groups. Results Two patients (10%) in group 1 and three patients (15.7%) in group 2 had clinical signs of infection. No statistically significant difference (p = 0.58) was seen in the incidence of infection in both the groups. Microbial load was positive in seven patients (35%) and six patients (30%) in group 1; four patients (21%) and three patients (15.8%) in group 2 on the 3rd and 7th post-operative day respectively. No statistical significance was seen with the presence of microbial load and clinical signs of infection in both groups. Conclusion After ORIF of single uncomplicated mandibular fractures, infection rates are the same with either short- or extended-antibiotic regimen.